2006
DOI: 10.1167/iovs.05-0685
|View full text |Cite
|
Sign up to set email alerts
|

Serum Autoantibodies to α-Fodrin Are Present in Glaucoma Patients from Germany and the United States

Abstract: Complex IgG antibody patterns against optic nerve antigens can be reproducibly identified in the serum of study populations from the United States and Germany. In both cohorts, patients with glaucoma have characteristic differences in serum autoantibody repertoires from those in control subjects. A newly described autoantibody to alpha-fodrin found in other neurodegenerative diseases such as Alzheimer's, further implicate a role for autoimmunity and the neurodegenerative processes in glaucoma. The high corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(80 citation statements)
references
References 44 publications
3
70
1
6
Order By: Relevance
“…Besides SS, α-fodrin is also present in the serum of patients with other related diseases, such as glaucoma and Graves' ophthalmopathy. 27,28 Thus, it is perhaps not surprising that a higher prevalence of α-fodrin positivity was detected in the NSS patients in the present study.…”
Section: Discussionsupporting
confidence: 50%
“…Besides SS, α-fodrin is also present in the serum of patients with other related diseases, such as glaucoma and Graves' ophthalmopathy. 27,28 Thus, it is perhaps not surprising that a higher prevalence of α-fodrin positivity was detected in the NSS patients in the present study.…”
Section: Discussionsupporting
confidence: 50%
“…(73)(74)(75) In glaucoma, the complex antibody profiles are stable and consistently exist among different study populations. (65) As described previously, many autoantibody reactivities are significantly increased or decreased in glaucoma patients as compared to non-glaucoma control group. Using a pattern recognition algorithm such as artificial neural networks for unique serum autoantibody patterns, it is possible to differentiate between sera of POAG patients and healthy subjects with a sensitivity and specificity of approximately 93%.…”
Section: Autoimmune Biomarkersmentioning
confidence: 55%
“…anti-GFAP, anti-14-3-3) could be detected in glaucoma patients. (59)(60)(61)(62)(63)(64)(65)(66)(67)(68) However, whether the autoantibodies have a causative effect or appear as an epiphenomenon of the disease is yet to be unraveled. The downregulations are possibly related to a loss of natural protective autoimmunity and a disbalance of naturally occurring autoantibodies promoting neurodegenerative processes.…”
Section: Autoimmune Biomarkersmentioning
confidence: 99%
“…6 they are then incubated with complex antigenic mixtures, which are recognized by the antibodies, eluted, and subsequently analyzed by SELDI-TOF or MALDI-TOF. Using this approach, specific antibody patterns in glaucoma patterns could be demonstrated [80].…”
Section: Biomarker Profiling: Seldi-tof and Clinprot Maldi-tofmentioning
confidence: 99%
“…These studies showed antibodies against, e.g., heat shock proteins [99], g-enolase [100], GST [101], glycosaminoglycans [102], and a-fodrin [80]. Studies of our group revealed significant differences in antibody patterns against ocular antigens in sera of glaucoma patients in comparison to healthy controls [80,[103][104][105][106]. We also analyzed antibody patterns against retinal antigens in the aqueous humor of normal tension glaucoma patients and found significant differences to the control group (accepted for publication) [107].…”
Section: Glaucomamentioning
confidence: 99%